2019
DOI: 10.1002/fsn3.1141
|View full text |Cite
|
Sign up to set email alerts
|

Effects of grape pomace and seed polyphenol extracts on the recovery of gut microbiota after antibiotic treatment in high‐fat diet‐fed mice

Abstract: The widespread use of antibiotics all over the world increases the risk of many metabolic diseases by altering the gut microbiota. Grape by‐products are of particular interest in the prevention of metabolic diseases, while only minimum amounts of these wastes are up‐graded or recycled at present. The study investigated the effect of grape pomace (GPE) and seed (GSE) polyphenol extracts on the recovery of gut microbiota after antibiotic cocktail treatment in high‐fat diet‐fed (HFD) mice. C57BL/6J mice were fed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 39 publications
(66 reference statements)
0
19
0
Order By: Relevance
“…Taken together, the improvement of FO intervention on AS may be due to the rectification of gut dysbiosis. In order to determine the crucial role of gut microbiota in the effectiveness of FO on the development of AS, as previously described ( 28 ), the AB cocktails were used to eliminate the effect of gut microbiota in ApoE −/− mice. After 3 weeks of AB cocktails, gut microflora was found with difficulty by 16S rRNA sequencing, demonstrating that mimic germ-free mice were successfully established.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taken together, the improvement of FO intervention on AS may be due to the rectification of gut dysbiosis. In order to determine the crucial role of gut microbiota in the effectiveness of FO on the development of AS, as previously described ( 28 ), the AB cocktails were used to eliminate the effect of gut microbiota in ApoE −/− mice. After 3 weeks of AB cocktails, gut microflora was found with difficulty by 16S rRNA sequencing, demonstrating that mimic germ-free mice were successfully established.…”
Section: Discussionmentioning
confidence: 99%
“…The HFD was prepared by the company in advance and was stored at 4 • C. After 12 weeks of FO treatment, we fasted the mice for 12 h, and then euthanized them for further analysis. In the second phase, according to previous reports (28), after 3 weeks of antibiotic (AB) cocktail (0.5 g/L vancomycin, 1 g/L neomycin sulfate, 1 g/L metronidazole, and 1 g/L ampicillin), the ABtreated male ApoE −/− mice (n = 24) were randomly divided into two groups (12 animals/group): MOD group (AB/MOD) and MOD-treated with FO group (AB/FO). After 12 weeks of HFD feeding, the mice were fasted for 12 h and then euthanized for further studies in consistence with the initial period of this study.…”
Section: Experimental Designmentioning
confidence: 99%
“…In another study, antibiotic therapy has been shown to alleviate glucose intolerance, inflammation and liver steatosis caused by HFd, along with reduced liver lipogenesis and increased heat production in subcutaneous white adipose tissue (43). The diversity of intestinal flora in HFd mice and mice treated with antibiotics in their drinking water was significantly reduced, altering the function of the flora in the host (79).…”
Section: Approaches and Rationale For The Use Of Fecal Microbiota Tramentioning
confidence: 98%
“…In a cohort study using FMT from patients to germ-free mice ( 78 ), it was observed that, compared with healthy controls, microbial richness and diversity were markedly decreased, and that the Prevotella genus dominated the gut enterotype, whereas reduced numbers of Prevotella bacteria were associated with a healthy status, and overgrowth of bacteria such as Prevotella and Klebsiella was observed in metagenomic and metabolomic analyses ( 79 ). A number of microbial CVD-specific biomarkers have been identified, and fecal microbiome-targeted strategies are currently considered as a powerful tool for early diagnosis and treatment of different diseases.…”
Section: Treatment Of Cvds Based On Intestinal Microflora and Theimentioning
confidence: 99%
“…Antibiotics are widely used in clinical setting to treat infectious diseases, although they have been found to alter the gut microbiota and increase the risk of many metabolic diseases. A study revealed that grape seed polyphenol extract had a positive influence on the recovery of gut microbiota after treatment with an antibiotic cocktail in high-fat-diet-fed mice [ 52 ]. In brief, grape exhibited a potent ability to modulate the gut microbiota, and polyphenols were found to play an important role in this ability.…”
Section: Health Benefits Of Grapementioning
confidence: 99%